Simultaneous Spectrophotometric Estimation of Nebivolol Hydrochloride and Hydrochlorothiazide in Tablets - Dhandapani, B.; Suresh Kumar, K.; Karthikeyan, R.; Raja, M.; Somasundaram, A. (Asian Journal of Chemistry, 2010)
Two simple, accurate and precise methods for simultaneous estimation of nebivolol hydrochloride (NEB-H) and hydrochlorothiazide (HCT) in combined dosage form have been described. First method employs formation and solving of Q-absorbance equation at 275 nm (isoabsorptive point) and at 282.5 nm (λmax of NEB-H). The second method involves formation and solving of simultaneous equation using 282.5 and 271.5 nm (λmax of HCT) using methanol as solvent. The result of analysis has been validated statistically and by recovery studies with standard deviation < 1.0 % was found. The proposed methods were successfully applied for estimation of nebivolol hydrochloride and hydrochlorothiazide in combined tablet formulation.